Analisis Moderasi Religiusitas Pada Pengaruh Pendidikan, Pengalaman dan Motivasi Terhadap Kinerja Pegawai Pemprov Sumut - Muslim Marpaung; M Ridwan; Sulastri Sriani; Purnama Ramadani Silalahi (ITB AAS INDONESIA Surakarta, 2021)
Abstract The low budget absorption capacity of Regional Apparatus Organizations (OPD) and cases of corruption involving government employees reflects the low awareness of employee religiosity and has an impact on the lack of performance of government employees. This study aims to analyze and evaluate the performance of employees within the Provincial Government of North Sumatra in terms of education, experience, motivation with religiosity as a moderating variable. This study uses a quantitative approach. Data analysis used the Moderated Regression Analysis (MRA) test. The results obtained that partially, experience and motivation have a significant effect on the performance of the North Sumatra Provincial Government employees. But partially, education has no significant effect on the performance of the North Sumatra provincial government employees. Simultaneously, education, experience and motivation have a significant effect on the performance of the North Sumatra Provincial Government employees. Meanwhile, Religiosity strengthens the influence of Education, Experience, and Motivation on Employee Performance.